2012
DOI: 10.1186/1471-2229-12-17
|View full text |Cite
|
Sign up to set email alerts
|

Organ specificity and transcriptional control of metabolic routes revealed by expression QTL profiling of source-sink tissues in a segregating potato population

Abstract: BackgroundWith the completion of genome sequences belonging to some of the major crop plants, new challenges arise to utilize this data for crop improvement and increased food security. The field of genetical genomics has the potential to identify genes displaying heritable differential expression associated to important phenotypic traits. Here we describe the identification of expression QTLs (eQTLs) in two different potato tissues of a segregating potato population and query the potato genome sequence to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…There were a high number of trans-eQTLs found on chromosome 5 indicating the presence of a master regulator of gene expression. The genome-wide pattern of eQTL was similar to results published by others using microarray data (Kloosterman et al, 2012) indicating that tag count gene expression data could produce similar results as microarrays. Inclusion of tags that were not unique to a single gene resulted in reduced cis-eQTLs (data not shown).…”
Section: Eqtl Analysissupporting
confidence: 84%
“…There were a high number of trans-eQTLs found on chromosome 5 indicating the presence of a master regulator of gene expression. The genome-wide pattern of eQTL was similar to results published by others using microarray data (Kloosterman et al, 2012) indicating that tag count gene expression data could produce similar results as microarrays. Inclusion of tags that were not unique to a single gene resulted in reduced cis-eQTLs (data not shown).…”
Section: Eqtl Analysissupporting
confidence: 84%
“…) and the potential importance of the circadian clock in the control of tuberization, supported by eQTL evidence, has previously been discussed (Kloosterman et al . ). Similar to Arabidopsis, expression patterns of CDF , GI , LHY and TOC1 in potato follow a diurnal rhythm (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Recent breakthroughs have identified that the timing of tuberization in potato is regulated by the circadian clock via the transcriptional regulation of CONSTANS (CO) controlling the synthesis and transport of a potato FLOWERING TIME (FT) ortholog associated with tuber induction termed StSP6A (Navarro et al 2011). The gene underlying a major quantitative trait locus (QTL) controlling the timing of tuberization has been identified as a CYCLING DOF FACTOR (CDF), a component of the circadian clock (Kloosterman et al 2013) and the potential importance of the circadian clock in the control of tuberization, supported by eQTL evidence, has previously been discussed (Kloosterman et al 2012). Similar to Arabidopsis, expression patterns of CDF, GI, LHY and TOC1 in potato follow a diurnal rhythm (Fig.…”
Section: Changes In Gene Expression Related To the Circadian Clock Comentioning
confidence: 98%
“…Expression QTL analysis identifies genomic regions that are likely to contain causal polymorphisms with regulatory effects on the genes being assayed. Large-scale, global eQTL mapping studies on a variety of plants have been published over the past decade, including maize (Schadt et al, 2003;Shi et al, 2007;Swanson-Wagner et al, 2009;Holloway et al, 2011;Li et al, 2013), Eucalyptus (Kirst et al, 2005), Arabidopsis (Keurentjes et al, 2007;Wentzell et al, 2007;West et al, 2007), wheat (Jordan et al, 2007), barley Potokina et al, 2008;Chen et al, 2010;Moscou et al, 2011), rice (Wang et al, 2010(Wang et al, , 2014, cotton (Claverie et al, 2012), potato (Kloosterman et al, 2012) and Populus (Drost et al, 2015). Several of these studies combined eQTL with QTL analysis to explore the genetic basis underlying phenotypic QTL; for example, Wentzell et al (2007) identified a candidate gene for glucosinolate accumulation in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%